(untitled) (Baghdad Science Journal, 2008)
In the present investigation, five derivatives were synthesized as potential antimicrobial agents , The compounds are : 2-amino 5-phenyl - 1,3,4- oxadiazole dithi-ocarbomate, 2-amino 5-( 4-amino- N,N-dimethyl phenyl)- 1,3,4- oxadiazole, 2-amino 5- (4-amino N,N- dimethyl phenyl)- 1,3,4- oxadizole dithiocarbamate, 2-amino 5-(4-nitr-ophenyl)-1,3,4-oxadiazole, 2-amino 5-(4-nirophenyl)-1,3,4- oxadiazole dithiocarbamate. The above newly synthesized compounds were investigated for their antibacterial, antifungal activities. The results of the biological revealed that the compounds activities against S.aureuss and B.subtilis and also P.aeureoginosa and Staph. Aureus. The prepared compounds were characterized by infrared spectrum, 1HNMR nuclear magnetic resonance and some physical properties.